Higher Education Faculty Characteristics and Opinions. NEA Research Memo. - National Education Association, Washington, DC.; National Education Association, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1979)
In spring 1978 National Education Association Research surveyed a national sample of college faculty to obtain estimates of their professional activities, working conditions, characteristics, and opinions. The findings reported here are based on responses from 803 faculty members, or 56.2 of those sampled. Among the findings: the median age of faculty is 43 years; 60.7 percent of faculty have doctorates; 37.5 percent have elementary or secondary teaching experience; the median work time is 50 hours per week in a 39-week work year; the median teaching load is 12 class hours per week with 80 students, and includes counseling responsibilities for 20 undergraduates and 5 graduate students; 27.6 percent report fairly low or very low morale; 50.9 percent believe morale to be declining; 26.1 percent see important constraints in effect on personal academic freedom; over two-thirds see a need for improvement of due process procedures at their institutions; and 80.2 percent are concerned about the number of part-time faculty members currently in higher education. Areas in which faculty voice a need for improvement include: communication of faculty concerns to legislatures, boards of directors, and institutional administrators; information about salaries paid to other faculty in the same institution; assistance in handling complaints with local administration; faculty representation in policymaking; institutional policies for faculty employment practices; salary levels and equity; and institutional financial support for faculty development. (Author/MSE)
Availability: National Education Association, 1201 16th St., N.W., Washington, DC 20036 (NEA members, $1.50, stock number 1666-1-00; nonmembers $3.25, stock number 1666-1-10).
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: College Faculty; Employment Practices; Faculty Advisers; Faculty College Relationship; Faculty Development; Faculty Promotion; Faculty Workload; Financial Support; Higher Education; National Surveys; Part Time Faculty; Personnel Policy; Policy Formation; Salary Wage Differentials; State Government; Statistical Data; Surveys; Tables (Data); Teacher Administrator Relationship; Teacher Attitudes; Teacher Characteristics; Teacher Morale; Teacher Salaries; Work Experience; Reports, Research; Numerical/Quantitative Data